JOB INSECURITY AND INTENTION TO STAY: THE ROLE OF WORK STRESS AND FRIENDSHIP SUPPORT - Feby Prayoga; Asep Gunawan; Dadang Priyono (Jurnal Maneksi, 2026)
Introduction: This study examines the effect of job insecurity on employees' intention to stay through work stress as a mediating variable, and tests the moderating role of friendship support on the relationship between job insecurity and work stress as well as between work stress and intention to stay, among operational employees of a plastic manufacturing company (PT XYZ) in Cirebon Regency.Methods: This research employs a quantitative approach. Primary data were collected from 177 operational employees determined through purposive sampling and the Yamane formula. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software, covering outer model and inner model evaluation.Results: The results show that job insecurity has no significant direct effect on intention to stay, but has a significant positive effect on work stress. Work stress has a significant negative effect on intention to stay and fully mediates the effect of job insecurity on intention to stay. Friendship support does not significantly moderate the effect of job insecurity on work stress, but significantly moderates (weakens) the negative effect of work stress on intention to stay. The moderated-mediation effect of friendship support on the overall indirect path is not supported.Conclusion and suggestion: These findings indicate that work stress is the central psychological mechanism explaining employee retention behavior under conditions of job insecurity, while friendship support functions effectively only as a buffer against work stress that has already emerged, not against the structural threat represented by job insecurity itself. Companies should strengthen contractual transparency and structural certainty while fostering a supportive social climate among coworkers. Keywords: Job Insecurity, Work Stress, Friendship Support, Intention to Stay, PLS-SEM